Guidelines for the quantification of classroom and laboratory areas in a collegiate-level school - Lim, Manuel III (Quezon City College of Architecture, University of the Philippines, Diliman, 1992)
An analytical approach to the quantification of classroom and laboratories in a college has been established. The system is not formulaic, where results are expected to be correct and immediately useful once data is given. However, the system creates an environment of awareness for the architect and the owner, thus being not only a method of determining the required quantities of classrooms and laboratories, but also a decision-making tool. The summary of points being presented by the body of work is as follows: that administrative policy plays a crucial part in determining the number of classrooms and laboratories required, specially in its influence on class schedules, utilization of rooms and operations; that the required number of classrooms must relate itself to the utilization rate, giving consideration to both physical provision and efficiency of use; that the class schedule is a main determinant on the effciency of use if utilization rate of the classrooms and laboratories of a college; that the educational worksheet, the concurrency table and the subsequent analysis can be organized into a guideline that can be tailored to respond to different needs and conditions of a college in its search for additional space, and as such, can not only provide quantification, but also information as well.
Thesis (Master of Architecture)--University of the Philippines Diliman.
Keywords: Classroom facilities; Laboratory facilities; School facilities